PENGAWASAN DAN PENGENDALIAN KEBIJAKAN PELARANGAN PAKAIAN IMPOR BEKAS (THRIFT) DALAM MELINDUNGI KEPENTINGN UMUM OLEH KEDEPUTIAN III KANTOR STAF PRESIDEN REPUBLIK INDONESIA - Immanuel, Revandy Eliazer; Johannes, Ayu Widowati (Institut Pemerintahan Dalam Negeri (IPDN), 2024)
This research focuses on the gap of the extant policy prohibiting imported used clothing that is also has been implemented but the distribution and trade of imported used clothing is still found. The goal of this research is to describe the form, reveal obstacles and support, and explain the strategy of the policy monitor and control by the Deputy III Executive Office of the President. Descriptive qualitative method through techniques of interview, observation, and documentation with data triangulation. Theory used is Policy Control from Nugroho (2018). Combined monitoring already conducted, evaluation based on field data and implementation reports, and there were recommendations as reward. Obstacles found: people still interested in obtaining imported used clothing; existence of mafia that consists of law enforcers; and monitor from external control and policy implementers is not yet intense. Supporting factor is the consistent leadership support. The strategy is to continue to implement monitoring of implementers emphasizing on grace period and to approach related institutions to conduct integrated monitoring. Maintaining the combined monitoring and multi-perspective evaluation is recommended as well as the influence strengthening of the reward. Special task force is needed to tackle the mafia as well as the necessity of the more anticipative strategy of monitor and control scheme.